Follow-up study on the long-term effectiveness of the home-visiting program “ProKind”: study protocol for a randomized controlled trial - Kliem, Sören; Sandner, Malte; Brand, Tilman; Fischer, Sebastian; Lohmann, Anna; Schepan, Marie Lisanne; Conti, Gabriella; Baier, Dirk (Frontiers in Pediatrics, 2025)
BackgroundThe Nurse-Family Partnership (NFP) is an evidence-based home visiting program shown to improve maternal and child outcomes. Pro Kind is the first German adaptation of NFP, implemented between 2006 and 2012. While earlier evaluations demonstrated short- and medium-term benefits, no European trial has yet assessed long-term effects into adolescence.ObjectivesThis study protocol outlines the third phase of the Pro Kind randomized controlled trial (RCT), designed to evaluate the program’s effectiveness 14–16 years post-intervention. Primary aims are to assess adolescent and maternal outcomes related to mental health, parenting, risk behaviors, and life satisfaction, as well as potential long-term economic effects.MethodsThe original RCT enrolled 755 pregnant women with psychosocial risk factors, randomly assigned to an intervention (n = 394) or control group (n = 361). The intervention comprised structured home visits from midwives or tandem teams (midwife + social worker) from pregnancy until the child’s second birthday. The 15-year follow-up combines self-report data (via online interviews and questionnaires) and administrative records on employment, social benefits, and criminal justice involvement. Discussion: This study represents the first long-term follow-up of an NFP adaptation in Europe. While U.S. trials of NFP provide evidence of the program’s effectiveness, these results cannot be generalized to European welfare contexts. This underscores the need for long-term evaluations of NFP adaptations in Europe to generate evidence that can inform policy and ensure evidence-based decision making.